2019
DOI: 10.1103/physrevd.99.103020
|View full text |Cite
|
Sign up to set email alerts
|

Ultralight dark matter in disk galaxies

Abstract: Analytic arguments and numerical simulations show that bosonic ultralight dark matter (ULDM) would form cored density distributions ("solitons") at the center of galaxies. ULDM solitons offer a promising way to exclude or detect ULDM by looking for a distinctive feature in the central region of galactic rotation curves. Baryonic contributions to the gravitational potential pose an obstacle to such analyses, being (i) dynamically important in the inner galaxy and (ii) highly nonspherical in rotation-supported g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 58 publications
(103 reference statements)
8
82
0
Order By: Relevance
“…The density profile of the dark matter core with baryons is well described by a ground state solution of the SP equation taking into account the additional gravitational potential sourced by the baryon density. Similar solitonic solutions with an additional gravitating component have been investigated in the context of supermassive black holes [28,34] and galactic disks [33]. Our simulations confirm and extend these results by providing evidence that modified ground state solutions are approached dynamically in the presence of baryonic feedback (Appendix B).…”
Section: Resultssupporting
confidence: 80%
“…The density profile of the dark matter core with baryons is well described by a ground state solution of the SP equation taking into account the additional gravitational potential sourced by the baryon density. Similar solitonic solutions with an additional gravitating component have been investigated in the context of supermassive black holes [28,34] and galactic disks [33]. Our simulations confirm and extend these results by providing evidence that modified ground state solutions are approached dynamically in the presence of baryonic feedback (Appendix B).…”
Section: Resultssupporting
confidence: 80%
“…4 and 5, respectively. The analysis of the cB211.072.64, for which we use seven values of t s with increased statistics, has clearly revealed that excited state effects die out slowly and that one needs to go to larger values of t s [35] keeping statistical errors small to see clear convergence as also demonstrated in Ref. [36].…”
Section: A Zero Momentum Transfersupporting
confidence: 59%
“…3. (35) summation method at around t low s ≃1 fm converges to the two-state fit result within errors. We take the two-state fit result as our final value for these two ensembles.…”
Section: A Zero Momentum Transfersupporting
confidence: 51%
See 1 more Smart Citation
“…The results are not yet conclusive, and depending on the analysis one may argue for the presence of a soliton object and a SF mass of around m a22 ≡ (m a /10 −22 eV) 1, or just an upper bound for the latter, m a22 < 0.4. More recently, the very presence of a soliton structure has been tested using data from rotation curves in galaxies, and then it is inferred that m a22 > 10 [60,61].…”
Section: Introductionmentioning
confidence: 99%